Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1981
DOI: 10.1111/j.1463-6395.1981.tb00623.x
|View full text |Cite
|
Sign up to set email alerts
|

Thread Cells from the Slime Glands of Hagfish (Myxinidae)

Abstract: Fernholm, B. 1981. Thread cells from the slime glands of hagfish (Myxinidae). Denmark.) -Acta zool. (Stockh.) 6 2 ( 3 ) : 137-145.Scanning electron microscopy and light microscopy demonstrate that the mature thread cells in Eptatretus deani and Myxine glutinosa consist of a single, coiled thread up to 10 cm long. Mature thread cells apparently loose the cell membrane within the slime gland before expulsion. Thus the old idea that rupture of the cell membrane causes the uncoiling in sea water is no longer tenab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
67
1

Year Published

1986
1986
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(72 citation statements)
references
References 12 publications
(2 reference statements)
2
67
1
Order By: Relevance
“…Thinking about the slime in this way is remarkably consistent with the hypothesis that the slime functions as a defence against gillbreathing predators (Fernholm, 1981;Martini, 1998). If the slime indeed evolved as something that could bind to gills and disrupt respiratory flow, one would not necessarily expect it to bind water irreversibly; slowing it down would be sufficient.…”
Section: A Model Of Hagfish Slime Structure and Mechanicssupporting
confidence: 51%
See 1 more Smart Citation
“…Thinking about the slime in this way is remarkably consistent with the hypothesis that the slime functions as a defence against gillbreathing predators (Fernholm, 1981;Martini, 1998). If the slime indeed evolved as something that could bind to gills and disrupt respiratory flow, one would not necessarily expect it to bind water irreversibly; slowing it down would be sufficient.…”
Section: A Model Of Hagfish Slime Structure and Mechanicssupporting
confidence: 51%
“…Hagfish slime differs from other animal slimes in that it contains not only slippery mucins, but also fine fibres, or 'slime threads', which are believed to lend it strength and cohesion (Downing et al, 1981b;Fernholm, 1981;Koch et al, 1991b). The slime is formed when specialized slime glands eject coiled threads (or 'skeins') and mucin vesicles into seawater (Fig.·2).…”
mentioning
confidence: 99%
“…Using SEM, Fernholm (Fernholm, 1981) observed fibrous structures bridging adjacent threads of intact skeins, but did not speculate on their significance. Our SEM analysis revealed that the same structures observed by Fernholm are present in stabilizing solutions, but not in unraveling treatments.…”
Section: Research Articlementioning
confidence: 99%
“…The slime is used as a defense mechanism against gill-breathing predators (Lim et al, 2006), and may be used for other functions as well (Fernholm, 1981;Zintzen et al, 2011). Its components are produced in and released from glands situated ventrolaterally along the length of the animal on both sides (Newby, 1946).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation